Room temperature ferroelectricity in donor-acceptor co-doped TiO2 ceramics using doping-engineering. (15th May 2018) - Yu, Yang; Wang, Li-Dong; Li, Wei-Li; Qiao, Yu-Long; Zhao, Yu; Feng, Yu; Zhang, Tian-Dong; Song, Rui-Xuan; Fei, Wei-Dong
Abstract: Conventional ferroelectric oxides are of generally non-centrosymmetric crystals resulting from paraelectric-ferroelectric transitions. Here, we present a new donor-acceptor ion co-doping route to room-temperature ferroelectricity in rutile TiO2, where ionic pair of co-doping ions plays very important roles in generating local broken symmetry and polarization. The (Nb + Al) co-doped TiO2 sintered with a two-step method exhibits ferroelectricity and piezoelectric response, and it is believed that Nb 5+ -Al 3+ pairs along TiO2 [001] direction play important role in the ferroelectricity. A large lattice distortion can be induced in the vicinity of the ionic pair, which results in local broken-symmetry. The relative displacements of cations and anions around the ionic pair, induced by the lattice distortion, cause the local polarization. The results and mechanisms presented in this work provide a new approach to the design of new ferroelectrics via doping engineering. Graphical abstract: Image 1